Insulin initiation in patients with type 2 diabetes is often delayed, but access to a diabetes nurse may help-insights from Norwegian general practice - Ibrahimu Mdala; Kjersti Nøkleby; Tore Julsrud Berg; John Cooper; Sverre Sandberg; Karianne Fjeld Løvaas; Tor Claudi; Anne Karen Jenum; Esben Selmer Buhl (Taylor & Francis Group, 2024)
AbstractObjective: We opted to study how support staff operational capacity and diabetes competences may impact the timeliness of basal insulin-initiation in general practice patients with type 2 diabetes (T2D).Design/Setting/Outcomes: This was an observational and retrospective study on Norwegian primary care patients with T2D included from the ROSA4-dataset. Exposures were (1) support staff size, (2) staff size relative to number of GPs, (3) clinic access to a diabetes nurse and (4) share of staff with diabetes course (1 and 2 both relate to staff operational capacity, whereas 3 and 4 are both indicatory of staff diabetes competences). Outcomes were 'timely basal insulin-initiation' (primary) and 'attainment of HbA1c<7%' after insulin start-up (secondary). Associations were analyzed using multiple linear regression, and directed acyclic graphs guided statistical adjustments.Subjects: Insulin naïve patients with 'timely' (N = 294), 'postponed' (N = 219) or 'no need of' (N = 3,781) basal insulin-initiation, respectively.Results: HbA1c [median (IQR)] increased to 8.8% (IQR, 8.0, 10.2) prior to basal insulin-initiation, which reduced HbA1c to 7.3 (6.8-8.1) % by which only 35% of the subjects reached HbA1c <7%. Adjusted risk of 'timely basal insulin-initiation' was more than twofold higher if access to a diabetes nurse (OR = 2.40, [95%CI, 1.68, 3.43]), but related only vaguely to staff size (OR = 1.01, [95%CI, 1.00, 1.03]). No other staff factors related significantly to neither the primary nor the secondary outcome.Conclusion: In Norwegian general practice, insulin initiation in people with T2D may be affected by therapeutic inertia but access to a diabetes nurse may help facilitating more timely insulin start-up.